Evaluating Entomopathogenic Nematodes as Biocontrol Agents Against Two Major Cockroach Species, Blattella germanica and Periplaneta americana, in Antalya, Türkiye - Aysegul Cengiz; Burak Polat; Sevval Kahraman Kokten; Ummuhan Aslan Bıckı; Cansu Calıskan; Samed Koc; Emre Oz; Serap Kocaoglu-Cenkci; Ozge Tufan-Cetin; Huseyin Cetin (Pathogens, 2025)
Cockroaches, particularly the German cockroach (Blattella germanica Linnaeus, Blattodea: Ectobiidae) and the American cockroach (Periplaneta americana (Linnaeus), Blattodea: Blattidae), are major public health pests due to their ability to transmit pathogens and develop resistance to chemical insecticides, including synthetic pyrethroids, which are widely used worldwide. Given the increasing resistance, entomopathogenic nematodes (EPNs) have emerged as a potential biological control alternative. This study evaluates the efficacy of three EPN species, Steinernema carpocapsae (Weiser), S. feltiae (Filipjev), and Heterorhabditis bacteriophora Poinar, against B. germanica and P. americana collected from different regions of Antalya, Türkiye. Laboratory bioassays were conducted under controlled conditions, testing five EPN concentrations (100, 250, 500, 750, and 1000 IJs/mL). The results showed that S. carpocapsae was the most effective, causing mortality rates of 46.7% to 100% in adult German cockroaches and 20% to 66.7% in nymphs, while S. feltiae and H. bacteriophora exhibited lower efficacy. American cockroaches showed higher resistance, with S. carpocapsae achieving a maximum mortality of 33.3% at the highest concentration, whereas S. feltiae and H. bacteriophora had no significant lethal effect. These findings suggest that S. carpocapsae could be a promising biological control agent for B. germanica, particularly in pyrethroid-resistant populations.